Альпин үүлдрийн ямааны зуны бэлчээр ашиглах чадвар - Д, Пүрэвдолгор; Т, Батсүх; Б, Бейсен; Ш, Баярсайхан; Д, Сангажав (Proceedings of the Mongolian Academy of Sciences, 2017)
“Alpine” goats are from Alpine mountain which is located in the middle of France and Switzerland. They have unique features of build. For instance: they have upright ears, red-brown color with a variety of spot, and they are big and they grow very fast. Besides they are hardy, they have good polytocous and they are a breed of goats which is leading milk production in the world. Mature goats are 60-65 kg averagely. While a goat is milked for 290 days in a year, a goat produces 1000 liters of milk, 38.6 kg of fat and 33.7 kg of protein, otherwise 1 liter of milk contains 3.7% fat and 3.2% protein. We are breeding of Alpine goats under semi pasture conditionin Arvaikheer soum of Uvurkhangai province. Averge weigth of mature bucks was 60-70 kg, and milk goats was 45-50 kg. Maximun biomass of summer pasture were 5.1 centner, in grass forb dominated pasture. Regarding to the nutrition of pasture plants organic matter were 87.9%, protein 14.1%, fiber 20.9%, MDS 10.6 MJ. Buck were grazed 3.3 kg and milk goat were grazed 2.9 kg during around 10 hours of day in grass-forb dominated pasture. Averge milk goat yield were 2 liter of summer pasture grazed. Regarding to rhe content of milk fat 3.4%, protein 3.2%, sugar 4.8%, minerals 0.8%, dry matter 0.7%.